The cold war. A study in U.S. foreign policy. [With: The sources of Soviet conduct by X (Ps. of G.F. Kennan)] (Harper & Row, 1972)
With bibliogr. First publ. in: "The New York Herald Tribune", and in: "Foreign Affairs". 1947.